1990
DOI: 10.1073/pnas.87.4.1352
|View full text |Cite
|
Sign up to set email alerts
|

Differential alterations of cortical glutamatergic binding sites in senile dementia of the Alzheimer type.

Abstract: Involvement of cortical glutamatergic mechanisms in senile dementia of the Alzheimer type (SDAT) has been investigated with quantitative ligand-binding autoradiography. The distribution and density of Na+-dependent glutamate uptake sites and glutamate receptor subtypes-kainate, quisqualate, and N-methyl-D-aspartate-were measured in adjacent sections of frontal cortex obtained postmortem from six patients with SDAT and six age-matched controls. The number of senile plaques was determined in the same brain regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
2

Year Published

1990
1990
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(24 citation statements)
references
References 42 publications
1
21
0
2
Order By: Relevance
“…Kainate binding is significantly reduced in the parahippocampal gyrus, while in a number of other hippocampal areas (e.g., dentate gyrus, CA3), the binding of ligand is minimally altered in AD [80]. In contrast to hippocampal regions, kainate receptor binding is significantly increased by approximately 70% in deep layers of the AD frontal cortex compared with controls and there is a positive correlation between kainate binding and the senile plaque number in deep cortical layers [82]. However, in caudate nucleus, kainate binding is unaltered [94].…”
Section: Ampa and Kainate Receptorsmentioning
confidence: 85%
See 1 more Smart Citation
“…Kainate binding is significantly reduced in the parahippocampal gyrus, while in a number of other hippocampal areas (e.g., dentate gyrus, CA3), the binding of ligand is minimally altered in AD [80]. In contrast to hippocampal regions, kainate receptor binding is significantly increased by approximately 70% in deep layers of the AD frontal cortex compared with controls and there is a positive correlation between kainate binding and the senile plaque number in deep cortical layers [82]. However, in caudate nucleus, kainate binding is unaltered [94].…”
Section: Ampa and Kainate Receptorsmentioning
confidence: 85%
“…In addition, the same group reported that there is also decreased ligand binding in the cerebellum in AD [81]. However, other studies have demonstrated that the binding of ligand is unaltered in frontal cortex [82] and increased in the infragranular layer [83].…”
Section: Ampa and Kainate Receptorsmentioning
confidence: 89%
“…Consistent with this is the finding that presynaptic Glu-containing terminals, as measured by the marker o- [ 3H]aspartate, appear to be decreased in AD (Proctor et al, 1988b;Simpson et al, 1988;Chalmers et al, 1990). Despite this decrement in presynaptic glutamatergic markers, postsynaptic elements remain largely intact (Mouradian et a!., 1988;Simpson et al, 1988;Cotman et al, 1989;Cowburn et al, 1989;Chalmers et al, 1990), although evidence to suggest that the glycine regulatory site of the N-methyl-D-aspartate (NMDA) receptor complex is abnormal has been found by some (Procter et al, 1989a, b;Steele et al, 1989), but not all investigators (Ninomiya et a!., .1990). These findings have led to the suspicion that some other endogenous metabolite may be playing a pathogenetic role in AD via action at Glu receptors.…”
mentioning
confidence: 65%
“…Various alterations were described concerning the density and binding capacity of EAA receptors in Alzheimer's disease brains (Chalmers et al 1990;Geddes et al 1992;Greenamyre et al 1987;Jansen et al 1990). In spite of some contradictory results in these studies, it seems reasonable to hypothesise that the excitotoxicity, mediated by EAA, may playa role in the neuropathobiology of Alzheimer's disease (Deutsch & Morihisa 1988;Greenamyre & Young 1989).…”
Section: Excitatory Amino Acid-induced Damagementioning
confidence: 99%